Chlorhexidine Bathing Strategies for Multidrug-Resistant Organisms: A Summary of Recent Evidence. Issue 3 (September 2020) - Gall, Elizabeth; Long, Anna; Hall, Kendall K.
Abstract : Objective: The aim of the study was to summarize the latest evidence for patient bathing with a 2% to 4% chlorhexidine gluconate solution to reduce multidrug-resistant organism (MDRO) transmission and infection. Methods: We searched 3 databases (CINAHL, MEDLINE, and Cochrane) for a combination of the key words "chlorhexidine bathing" and MeSH terms "cross-infection prevention, " "drug resistance, multiple, bacterial, " and "drug resistance, microbial." Articles from January 1, 2008, to December 31, 2018, were included, as well as any key articles published after December 31. Results: Our findings focused on health care–associated infections (HAIs) and 3 categories of MDROs: methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), and carbapenem-resistant Enterobacteriaceae (CRE). Chlorhexidine bathing reduces MRSA acquisition and carriage, but not all studies found significant reductions in MRSA infections. Several studies found that chlorhexidine bathing reduced VRE acquisition and carriage, and one study showed lower VRE infections in the bathing group. Two studies found that bathing reduced CRE carriage (no studies examined CRE infections). Two very large studies (more than 140, 000 total patients) found bathing significantly reduced HAIs, but these reductions may be smaller when HAIs are already well controlled by other means. Conclusions: There is a high level of evidence supporting chlorhexidine bathing to reduce MDRO acquisition; less evidence is available on reducing infections. Chlorhexidine bathing is low cost to implement, and adverse events are rare and resolve when chlorhexidine use is stopped. There is evidence of chlorhexidine resistance, but not at concentrations in typical use. Further research is needed on chlorhexidine bathing's impact on outcomes, such as mortality and length of stay.